Introduction - of Gender and Law, Columbia Journal (Columbia Journal of Gender and Law, 2010)
The Columbia Journal of Gender and Law is pleased to announce that it has brought together volume 19.3 and 19.4 to present the total symposium publication, Gender on The Frontiers: Confronting Intersectionalities. This Symposium publication brings together thirteen scholars to comment on the intersection between gender, sexual orientation and other statutes, identities and modalities. By “confronting intersectionalities,” the Symposium authors expand upon the seminal writings of Kimberl6 Crenshaw’ and explore the ways that race, class, gender and sexual orientation collectively inform people’s lived experiences under the system of laws. In examining “gender on the frontiers,” the Symposium writers examine the frontier in both its literal and figurative dimensions-analyzing citizenship and belonging; borders and exclusion, and the societal and legal regulation of bodies. While the articles featured address a common theme, the authors’ approaches are diverse, demonstrating that gender and sexuality studies is not just a discipline, but a lens, one which illuminates fields as varied as law, political science and performance studies. For ease of reference, the articles are organized alphabetically in each issue by author name but the many dialogues connecting the authors are various. This introduction hopes to illuminate some of those connections and brief summarize each article.